An Investigation of Managers' Adaptations to SFAS No. 2: Accounting for Research and Development Costs - Selto, Frank H.; Clouse, Maclyn L. (Journal of Accounting Research, 1985)
Frank H. Selto, Maclyn L. Clouse, An Investigation of Managers' Adaptations to SFAS No. 2: Accounting for Research and Development Costs, Journal of Accounting Research, Vol. 23, No. 2 (Autumn, 1985), pp. 700-717